Lower sanctions, greater antitrust compliance? Cartel conduct with imperfect information about enforcement risk - Johannes Paha (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
This article provides a model of two risk-neutral firms that may cooperate to achieve a goal that is potentially illegal. The model assumes enforcement risk and firms that are imperfectly informed about antitrust law enforcement. It is shown that compliance training, which educates the agents about law enforcement, may prevent hardcore cartels. Compliance training programs may also promote forms of cooperation that are beneficial for customers. The article shows that a competition authority can sometimes spur the implementation of compliance programs by imposing lower sanctions on wrongdoers.
Keywords: K21; K42; L41; 330